Strategi Koping dan Depresi pada Mahasiswa yang Praktek Klinik Keperawatan saat Pandemi COVID-19 - Esti Widiani; Ira Rahmawati; Nurul Hidayah (Ners Jurnal Keperawatan, 2023)
Against the backdrop of the COVID-19 pandemic, the demands placed on nursing students during clinical practice have necessitated a heightened level of professionalism. Paradoxically, this intensified clinical environment has also given rise to increased rates of depression among nursing students, compounding the preexisting challenges they face. This study is driven by the objective of investigating the correlation between coping strategies and depression among nursing students actively engaged in clinical practice during the COVID-19 pandemic. A total of 373 nursing students participated in this cross-sectional study. The assessment of depression among the respondents was carried out using the Patient Health Questionnaire (PHQ-9). Coping strategies were evaluated through the application of the Coping Orientation to Problems Experienced Inventory (Brief-COPE). The results yielded significant insights, with the coping strategy of reframing (p=0.009) demonstrating a noteworthy correlation with depression. In the realm of emotion-focused coping strategies, while the acceptance subscale (p=0.310) did not exhibit a significant correlation with depression, emotional support (p=0.037), venting (p=0.000), humor (p=0.000), and self-blame (p=0.003) all displayed notable correlations with depression. Furthermore, within the domain of avoidance coping, self-distraction (p=0.000), denial (p=0.008), substance use (p=0.000), and behavioral disengagement (p=0.000) subscales were also found to be significantly correlated with depression. nThese findings underscore the paramount importance of fostering adaptive coping strategies and emphasize the pivotal role of clinical instructors in preparing and bolstering students to effectively manage their emotional well-being during clinical practice, particularly within the challenging context of the COVID-19 pandemic.